ANALISIS KINERJA KARYAWAN BUMDes DI KABUPATEN KAMPAR - Jonnius Jonnius (Lembaga penelitian dan pengabdian kepada masyrakat, 2015)
This study was conducted to determine the performance of existing employees BUMDes in Kampar regency and the influence of potential competence, competence and motivation reality on the performance of the employee. The study population was all employees of 28 BUMDes, which were all made using the total sample or sampling. The data used are primary data obtained through questionnaires and interviews. Furthermore, analysis with a quantitative approach with the help of Microsoft Excel and SPSS statistical software version. 17.0. The results showed that the performance of employees, competence potential, competent and motivated employees BUMDes reality is included in the high category. Another finding is the reality of competence and motivation have a significant effect on the performance of employees, while the potential competence showed no significant effect. The third independent variable showed a fairly strong relationship with the dependent variable, as well as determination test showed 44.4% of the variation in employee performance can be explained by variations in the potential of variable competence, competence and motivation reality, while the remaining 55.6% is explained by factors other than three variables